ANALISIS KEMACETAN LALU LINTAS DI RUAS JALAN PROF. DR. H. ALOE SABOE KOTA GORONTALO (STUDI KASUS RUAS JALAN PASAR MOODU) - Pobela, Dira Sucilya; Akbar, La Ode Juni (Universitas Bina Taruna Gorontalo, 2022)
The city of Gorontalo is an area that has the potential to develop and compete with other regions, one of which is in terms of development in the field of transportation, especially regarding land transportation. The road is a means of transportation that is very important for human survival. On several roads in Gorontalo the ability to walk is still very limited, one of which is on Jalan Prof. Dr. H. Aloe Saboe Gorontalo City (precisely on the Moodu market road section where every Monday there is always a weekly market which causes congestion on the road, considering that Monday is a busy day. That's why the author took the research title